Muscle quality index and hyperuricemia: adipose tissue as a mediator - Shao, Ya; Wang, Yu; Jiang, Xuelian; Shao, Meiling; Liu, Bin; Li, Longti; Zhong, Huiqin (Frontiers in Endocrinology, 2025)
ObjectiveThe relationship between the Muscle Quality Index (MQI) and hyperuricemia remains incompletely defined, and additional studies are necessary to elucidate the mediating role of adipose tissue in this association.MethodsThis study utilized data from the 2011–2014 National Health and Nutrition Examination Survey (NHANES) and included 5,198 adults. MQI was calculated as the ratio of maximum handgrip strength to appendicular skeletal muscle mass (ASM), and adipose tissue parameters included body fat percentage (BF%) and visceral fat mass (VFM). To examine the link between MQI and hyperuricemia, multiple logistic regression models were employed, and generalized additive models were utilized to assess potential non-linear patterns. Mediation analysis was performed to assess the mediating effect of adipose tissue, and sensitivity analyses, which involved altering the thresholds for hyperuricemia and excluding individuals with major chronic conditions, were carried out to verify the consistency of the results.ResultsWhen treated as a continuous variable, MQI demonstrated a strong inverse association with hyperuricemia. Each one-unit increment in MQI corresponded to a 50% decrease in the odds of hyperuricemia (OR: 0.50, 95% CI: 0.43–0.57). Quartile-based analysis revealed that individuals in the highest MQI quartile had a 68% lower odds of developing hyperuricemia compared to those in the lowest quartile (OR: 0.32, 95% CI: 0.25–0.41). Subgroup analyses confirmed this negative correlation across various strata, and sensitivity analyses showed consistent results. Mediation analysis indicated that BF% and VFM explained 49.32% and 53.62% of the association between MQI and hyperuricemia, respectively.ConclusionThis study reveals a significant negative correlation between MQI and hyperuricemia, mediated by adipose tissue. These findings suggest that improving muscle quality and managing adipose tissue could offer new strategies for mitigating hyperuricemia and promoting better public health outcomes.